The Effect of Financial Sector Development on Poverty Reduction in Nigeria: An Empirical Investigation - Saidu, Ishaq; Marafa, Abbas Abdullahi (International Journal of Economics and Financial Issues, 2020)
This paper examines whether financial services (McKinnon conduit) or provision of credit is more effective in reducing poverty in Nigeria using data for the period 1980-2018. It employs Autoregressive and Distributed Lag Model (ARDL) Approach to estimate the parameters and cointegration analyses for income and consumption models. The results of the ARDL Bound Test to Cointegration indicate a long-run relationship among the variables in the two models. The study reveals that availability and improvement in financial services is more beneficial than credit growth. In addition, the study suggests that financial instability may hurt the poor and retards the beneficial effect of financial development particularly in the short run. The paper recommends intensification of effort towards second-generation reforms, such as, design and implementation of financial inclusion policies that involve improving access to financial services that foster inclusive-growth. Furthermore, the study recommends guided deregulation in credit market as a way of precluding or subduing its susceptibility in triggering full-blown crises that is detrimental to the poor’s aggregate welfare. Keywords: Financial Sector Development, Poverty Reduction, ARDL Model, Nigeria. JEL Classifications: E51, E52, C52, E65 DOI: https://doi.org/10.32479/ijefi.9532